2020
DOI: 10.7759/cureus.8598
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Anxiety and Suicidal Behaviors in American Adolescents With Major Depression

Abstract: The aim of this study was to evaluate the odds of association between suicidal behaviors and comorbid anxiety disorders in adolescents with major depressive disorder (MDD). Methods We included 122,020 adolescent inpatients with MDD from the Nationwide Inpatient Sample (NIS) and further grouped them by co-diagnosis of anxiety disorders. Logistic regression analysis was used to evaluate the odds ratio (OR) of suicidal behaviors due to comorbid anxiety disorders. Results Out of total MDD inpatients, 45.8% had com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Major risk factors are being female, being of African American descent, exposure to bullying and violence, sexual orientation, alcohol and substance abuse, psychiatric comorbidities, poor familial, and social support [8]. SUD often coexist with psychiatric illnesses and further increases the suicide risk [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Major risk factors are being female, being of African American descent, exposure to bullying and violence, sexual orientation, alcohol and substance abuse, psychiatric comorbidities, poor familial, and social support [8]. SUD often coexist with psychiatric illnesses and further increases the suicide risk [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with that of a recent study, which showed no statistically significant correlation between MDD with comorbid anxiety and suicidal behavior. 67 Although the results of our study add to the understanding of suicide risk in adolescent patients with MDD, several limitations need to be considered. First, the data were collected using a cross-sectional study design, making it impossible to determine the direction of a causal relationship between nightmare stress and suicide risk.…”
Section: Discussionmentioning
confidence: 97%
“…This result is consistent with that of a recent study, which showed no statistically significant correlation between MDD with comorbid anxiety and suicidal behavior. 67 …”
Section: Discussionmentioning
confidence: 99%
“…(3) Anxiety disorders themselves are not always associated with a higher prevalence of suicidal behavior; however, when they occur concomitantly with other psychiatric comorbidities, such as depressive disorders, they result in a summative effect on suicide risk. (20,22) The hypothesis of a summative effect on the risk of suicide caused by the co-occurrence of depressive symptoms and posttraumatic stress disorder symptoms was also observed in Chinese graduate students. (16) Use of substances such as alcohol and psychotropic drugs, and eating problems, depending on their severity, are also serious mental distress problems, especially when they occur during graduate studies, as they are associated with a higher risk for suicidal behavior in this population segment.…”
Section: Discussionmentioning
confidence: 97%